2022
DOI: 10.3390/kidneydial2020020
|View full text |Cite
|
Sign up to set email alerts
|

Ren.Nu, a Dietary Program for Individuals with Autosomal-Dominant Polycystic Kidney Disease Implementing a Sustainable, Plant-Focused, Kidney-Safe, Ketogenic Approach with Avoidance of Renal Stressors

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited cause of renal failure and has limited pharmacological treatment options. Disease progression is relentless, and regression is not a known feature of ADPKD even with pharmacological intervention. Recent research has uncovered underlying pathogenic mechanisms that may be amenable to dietary interventions. Cyst cells in ADPKD are thought to depend on glucose for energy and are unable to metabolize fatty acids and ketones. High-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Adherence (ketone concentrations), feasibility and secondary outcomes including TKV, and BMI will be evaluated. Based on these findings, Bruen and collaborators have designed a plant-focused ketogenic diet (Ren.Nu diet) for ADPKD based on the theory that a diet high in carbohydrate and animal protein might accelerate disease progression ( Bruen et al, 2022 ). A preliminary beta test was conducted for 12 weeks in 24 ADPKD patients and with the obvious limitations of the study (no control, selection bias, self-reporting).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence (ketone concentrations), feasibility and secondary outcomes including TKV, and BMI will be evaluated. Based on these findings, Bruen and collaborators have designed a plant-focused ketogenic diet (Ren.Nu diet) for ADPKD based on the theory that a diet high in carbohydrate and animal protein might accelerate disease progression ( Bruen et al, 2022 ). A preliminary beta test was conducted for 12 weeks in 24 ADPKD patients and with the obvious limitations of the study (no control, selection bias, self-reporting).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
“…A preliminary beta test was conducted for 12 weeks in 24 ADPKD patients and with the obvious limitations of the study (no control, selection bias, self-reporting). Preliminary data suggest reasonable adherence and feasibility ( Bruen et al, 2022 ).…”
Section: Cholesterol Reducing Agentsmentioning
confidence: 99%
“…Individuals with autosomal dominant polycystic kidney disease (ADPKD) may benefit from calorie restriction or ketogenic diet 19 130 131. This chronic progressive condition is characterized by hyperproliferation, inflammation, fibrosis, and cyst growth, leading to deterioration of kidney function over time 19 132.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a retrospective observational study of ADPKD patients who self-initiated ketosis either using ketogenic or time-restricted diets reported improvement in eGFR after 6 months 134. A pilot study on 24 patients with ADPKD demonstrated the feasibility of the ketogenic diet, reporting high adherence rates and improvements in blood pressure, eGFR, and kidney pain 130. In another exploratory RCT, 66 participants with ADPKD were randomized to ketogenic, water fasting, or control diets.…”
Section: Introductionmentioning
confidence: 99%
“…In ADPKD, animal experiments have shown potential of ketogenic dietary interventions ameliorating disease progression [5] and first data in humans point towards potential translatability of this approach [6,7]. In this Special Issue, Bruen et al [8] provide a first insight into a potential tailored dietary intervention that may enable the implementation of ketogenic dietary interventions in real life in the future. This aspect is complemented by recent evidence on the role of weight reduction in ADPKD.…”
mentioning
confidence: 99%